Ensuring Competency: Quality Assurance in High-Stakes Assessments in Medical Education - Nawaz, Qudsia; Ghaffar, Sadia A; Shafiq, Sadia; Tufail, Shazia; Rehman, Mounazza; Khan, Junaid Sarfaraz (Biological and Clinical Sciences Research Journal, 2025)
Quality assurance (QA) is fundamental in maintaining the validity, reliability, and fairness of assessment systems in medical education. With high-stakes assessments significantly influencing certification, licensure, and patient safety, robust QA mechanisms are essential to ensure the competence of future healthcare providers. Objective: To critically evaluate the role and application of quality assurance in high-stakes assessments within medical education, and to analyze its alignment with general assessment principles and its impact on educational outcomes and patient care. Methods: An analytical essay was developed through a comprehensive literature review spanning January 2009 to May 2024. Databases including PubMed and Google Scholar were used to retrieve peer-reviewed literature using the following keywords: quality assurance in higher education, quality assurance in medical education, competence in medical education, and high-stakes assessments in medical education. Selection criteria emphasized relevance, recency, and applicability to high-stakes medical assessments. Themes were synthesized and analyzed for critical insights and implications. Results: The literature reveals several key QA-related themes in high-stakes medical assessments. These include the need for standardized assessment formats, rigorous validation processes, continuous faculty development, transparent governance, and mechanisms for feedback and reform. Effective QA aligns closely with general principles of assessment, such as validity, reliability, fairness, and feasibility. QA is also vital across all domains of assessment—written, performance-based (OSCEs), and workplace-based assessment—ensuring defensible results that withstand scrutiny from regulatory bodies and stakeholders. Conclusion: Quality assurance is indispensable in high-stakes medical assessments. By embedding QA processes in every stage of assessment design, delivery, and review, medical institutions can ensure the production of competent graduates and uphold public trust in the medical profession. The development and enforcement of rigorous QA frameworks are therefore essential for the continuous improvement of medical education standards and patient safety.